Analysis of the Economic Impact of Meteorological Disasters on Tourism: The Case of Typhoon Morakot's Impact on the Maolin National Scenic Area in Taiwan. (February 2014) - Liu, Tzu-Ming
This study explores the cost of extreme weather disasters to the tourism industry, taking the Taiwan Maolin National Scenic Area as an example. The paper evaluates the economic damage caused by typhoon Morakot. The author uses long-term tourist trend lines as the basis for calculating disaster losses and adopts an error correction model as a measurement method for the estimation. The study finds that the entire park lost over 700, 000 visitors in the year and a half after the disaster, representing a loss of NT$1.39 billion in tourism business – a value three times the infrastructure loss. Any delays in reconstruction will increase the losses to the tourism industry. However, several tourist spots were gradually losing their attractiveness even before the disaster, and hastening to rebuild such sites is not conducive to the recovery of tourism. Rather, efforts should first be made to understand the reasons why these tourist spots were becoming less attractive and to gauge tourist demand for them before their reconstruction.